Evaluation of the Remdesivir Treatment of Non-Hospitalized Patients with COVID-19 - Fazal Hanan, Mohsina Haq, Ashfaq Ahmed, Bakht Biland, Ihteshamul Haq, Said Munir, Habib Ullah, (Pakistan Journal of Medical & Health Sciences, 2022)
Novel corona virus 2019 has resulted in a pandemic which killed over five million people worldwide. It causes acute respiratory syndrome and is reported to affect multi-organ system. Various variant of corona virus (COVID-19) has been emerged in various regions of the world as a result of mutation in original strains. The Purpose of the Current Study to evaluate the effect of Remdesivir for treating non-hospitalized patients with COVID-19 at the Department of Medicine PIMS Hospital from 1st January 2021 to 30th June 2021. In the Current Research One hundred patients were enrolled and divided into group A and group B within the age of 24-70 years. Group A was receiving Remdesivir while group B is not receiving Remdesivir. The clinical variables, BMI, Comorbidities, duration of disease severity and viral load were determined. RT-PCR was conducted to determine viral load. The mean age of study participants was 50±15 years with greater number of males. Diabetes was the major comorbidity. The time duration was decreased in group A upto 5 days and 8 days in group B. The viral load was decreased by mean value 6.32±1.76 to 6.2±1.78 in group B then group A respectively and result show that Remdesivir is effective in COVID-19 treatment. Keywords: Remdesivir, COVID-19, Viral load